Optimization of Culture Medium for Exopolysaccharide Production by Enterobacter cloacae Z0206 Using Response Surface Methodology - Jin, M.L.; Wang, Y.M.; Huang, M.; Lu, Z.Q.; Wang, Y.Z. (Asian Journal of Chemistry, 2011)
The quantitative effects of maltose, tryptone and beef extract concentration in the medium on yield of exopolysaccharide produced by Enterobacter cloacae Z0206 were investigated using response surface methodology. The experimental data obtained were fitted to a second-order polynomial equation using multiple regression analysis and also analyzed by appropriate statistical methods. By solving the regression equation and analyzing the response surface contour plots, the optimal medium was determined: maltose 37.150 g/L, tryptone 5.101 g/L and beef extract 5.627 g/L. Under the optimal conditions, the corresponding response value predicted for exopolysaccharide production was 12.950 g/L of fermentation liquor, which was also verified by validation experiments.